Forest habitat loss and human land use alter predation of artificial ground nests - Holopainen, Sari (Elsevier B.V., 2026)
Anthropogenic disturbances including forestry, urbanisation and agricultural expansion are causing significant habitat loss and fragmentation in boreal forests, leading to changes in ecosystem function. Here, we ask whether these anthropogenic disturbances alter predator–prey spatial overlap in the boreal forest landscape, leading to increased nest predation rates on ground-nesting birds such as forest grouse. To study the roles of forest loss and fragmentation on nest survival, we conducted an artificial nest predation experiment in Finland using 370 camera traps across landscapes varying in forest quantity and fragmentation (measured by edge habitat length). Our artificial nests mimicked the early egg-laying stage of forest grouse. Our primary hypotheses were that nest survival is higher in landscapes with more continuous forest habitat and less edge habitat, and that predator communities differ based on the matrix habitat between the forests. Our findings revealed a negative association with forest cover and nest predation risk, but forest fragmentation, measured as edge length, had no detectable relationship with the nest predation risk. Additionally, nest predation risk depended on the matrix habitat types, with agricultural land and urban areas exhibiting higher predation rates than clearcuts exhibited. Furthermore, the number of predator species observed was positively associated with the level of urban area present. We found that the raccoon dog (Nyctereutes procyonoides), a rather novel invasive alien species, was the most common mammalian nest predator, indicating a change in the predator community. Our results highlight the possible impact of both forest loss and the presence of agricultural and urban areas in the landscape on avian nest survival in forest habitats. We conclude that forest loss may be a more important factor affecting nest predation risk than forest fragmentation.